2015
DOI: 10.1177/1362480614565849
|View full text |Cite
|
Sign up to set email alerts
|

Strategic masculinities: Vulnerabilities, risk and the production of prison masculinities

Abstract: Expressions of masculinity in prison are most often characterized as being structured in response to an environment that encourages displays of stoicism, bravery, physical prowess and violence/aggression. However, we found that the antagonistic, precarious and risk-prone environment of the prison shapes prisoners' behaviours and the constitution of 'normative' and hegemonic masculinities in more nuanced ways than prior research suggests. Drawing on in-depth interviews with 56 male parolees, we explored how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 52 publications
5
111
0
Order By: Relevance
“…Empathy for the high degree of variability of gender identity provides a space in which the presence of trans prisoners in the recruits’ imaginings does challenge, in varying ways, the hypermasculine prison environment which relies on highly specific ways of ‘doing’ masculinities (see Ricciardelli ; Ricciardelli, Maier and Hannah‐Moffat ). Yet, as participant 33 indicates, ‘the gray area’ in which there is a highly diverse category of trans people remained a troubling area:
I struggle with it.
…”
Section: The ‘Gray Area’: Interpretations Of the Diversity Of Trans Imentioning
confidence: 99%
“…Empathy for the high degree of variability of gender identity provides a space in which the presence of trans prisoners in the recruits’ imaginings does challenge, in varying ways, the hypermasculine prison environment which relies on highly specific ways of ‘doing’ masculinities (see Ricciardelli ; Ricciardelli, Maier and Hannah‐Moffat ). Yet, as participant 33 indicates, ‘the gray area’ in which there is a highly diverse category of trans people remained a troubling area:
I struggle with it.
…”
Section: The ‘Gray Area’: Interpretations Of the Diversity Of Trans Imentioning
confidence: 99%
“…This became clear in a conversation with a Prison Team member, who stressed how contact with a disadvantaged group, such as prisoners, is inextricably linked with outreach legal aid: '… we're convinced that our outreach work, the fact that we visit the prisons, is of great significance and value because only a handful of people call us, but if we come to them-reach out to them-it's easier for them to contact us', (Field notes, Olesen). Criminological studies support the view that some prisoners regard public authorities with distrust and hostility (Ricciardelli et al 2015;Minke 2012;Olesen 2013), while legal aid research has shown that disadvantaged groups, regardless of their living situation and complex problems, may avoid taking legal action if they have previously had bad experiences with the police and/or legal institutions (Genn 1999;Carlin and Howard 1965;Sejr 1977). Thus, to improve prisoners' access to justice, the Juss-Buss Prison Team visits prisons in and around Oslo on a weekly basis.…”
Section: 'Troubles-talks'mentioning
confidence: 99%
“…Hegemonic masculinity has no meaning without the recognition of subordinate, compliant, and complementary notions of femininity and the systems of legitimation that create the hierarchical relations between (Messerschmidt ). Accordingly, hegemonic masculinity is ‘constructed in relation to, and occupies a position of superiority over, femininities and all other masculinities, legitimising the hierarchical structure of gender relations by ensuring that subordinate masculinities are positioned at the bottom of the gender hierarchy’ (Ricciardelli, Maier and Hannah‐Moffat , p.494).…”
Section: Literature Reviewmentioning
confidence: 99%